PENGARUH PROFITABILITAS TERHADAP RETURN SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN KOSMETIK DAN KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Nyoman Ayu Dewi Widiastini; Hermanto Hermanto; Siti Aisyah Hidayati (Master of Management, Mataram University, 2019)
This study aims to analyze the effect of profitability on stock returns with capital structure as a moderating variable in cosmetic and household needs companies listed on the Indonesia Stock Exchange (IDX). The data analysis technique in this study is inferential statistics (linear regression) using MRA, with a significant level of 5 percent using the SPSS program. The results of this study indicate that ROE has a positive and significant effect on stock returns. DER is not able to moderate the effect of ROE on stock returns in cosmetic companies and household needs for the 2011-2018 period.Keywords:ROE, Return Saham, DER